Red ginger wedang to strengthen immune system against covid-19 of children living in an orphanage - Sinamo, Karina Nola; Hutabarat, Nauas Domu Marihot Romauli (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The outbreak of the corona virus has forced orphanage children to gather at home to carry out learning and playing activities. The activity of gathering in one house can cause a high risk of Covid-19 transmission. The implementation of the community service program carried out by lecturers from the Food Science and Technology Department, Faculty of Agriculture, Universitas Sumatera Utara is a training for making red ginger wedang at LKSA Anak Gembira, Medan Tuntungan, Medan. Red ginger wedang is a drink that is healthy and refreshing for the body, where the aim of this training is that partners can practice it and consume it to maintain their immune system at LKSA Anak Gembira in preventing Covid-19. The training activity for making red ginger drink was attended by 24 people consisting of 2 orphanage owners and 22 orphanage children. After that, the consumption of red ginger was carried out and questionnaires were administered to measure the level of understanding of the benefits and preferences of the respondents towards red ginger after the training was held. The results of the questionnaire show that 93% respondents understand the benefits of red ginger for health and 87% like red ginger wedang.